2018
DOI: 10.1007/s11469-018-9872-1
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Problem Video Gaming in Urban and Non-urban Regions

Abstract: The purpose of this paper is to explore the differences in adolescent problem video gaming in a large urban area (Toronto) compared to a non-urban region of Ontario (Northern Ontario). The results of this study showed that 76.6% of adolescents in the urban region and 80.3% of adolescents in the non-urban region played video games in the past year (n = 2175). Adolescents in the urban region were significantly more likely than adolescents in the non-urban region to experience problem video gaming (16.7 and 8.8%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Shi et al [3] suggested that excessive use of videogames during school years is a risk factor associated with physical, social and cognitive health problems. Van Rooij et al [4] identified the main potential harms as being eye problems and hormonal changes, in addition to cognitive disorders that are associated with stress and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [3] suggested that excessive use of videogames during school years is a risk factor associated with physical, social and cognitive health problems. Van Rooij et al [4] identified the main potential harms as being eye problems and hormonal changes, in addition to cognitive disorders that are associated with stress and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Authors such as Chacón-Cuberos et al [ 4 ] or Verheijen et al [ 5 ], indicate that parents have little control over their children’s use of this kind of technology, due to its rapid spread throughout society. The problematic use of video games in schoolchildren is also a risk factor for diverse health problems at the cognitive, social, and physical levels [ 6 , 7 , 8 ]. A great deal of research has analyzed the negative consequences of the problematic use of video games.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of evidence published in Chinese reported that urban adolescents were 2 times more likely to develop IGD and other various problems than rural adolescents [18]. These may be due to larger communities in urban areas could lead to a weaker social cohesion, individualism, and a diminished sense of kinship than in rural areas [19], [20].…”
Section: B -Clinical Sciences Neurologymentioning
confidence: 99%